Centro de investigación gestión de ecosistemas sabaneros - plan parcial diafragma de servicios y gestión ambiental en Sabana Occidente (2019)
For this city of Bogotá a plan of urban-rural renovation is proposed, which from a more global perspective is established as a main axis that consolidates the territory understanding what is present today, and in this way complement what is found today. In the western region, articulating the other municipalities with this axis seeks to create competitive cities and in addition to this resilient, this word being understood as the ability of cities to recover by themselves after a catastrophe. The proposal of both the work and the architectural theme has as a priority to establish an inclusive project thought of by people and for them since they are the initial user and the final user of the project.